Correction to: Associations between change in labour market policies and work stressors: a comparative longitudinal survey data analysis from 27 European countries - T. Lunau; M. Wahrendorf; N. Dragano; J. Siegrist; K. A. van der Wel; M. Rigó (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.